Cephalopods in the diet of keystone-species animals in the region of the Argentine Islands Archipelago (West Antarctica) - Dykyy, І.; Zahorodnyi, I. (Український антарктичний журнал, 2019)
Оbjective. The study of diet of keystone-species vertebrates (Nothotenia coriiceps, Phalacrocorax bransfieldensis, Leptonychotes weddellii) in the ecosystem of the Argentine Islands Archipelago.